Konsumenters inställning till ett slopat beteskrav - Gustafsson, Gulli (2021)
There are three primary behaviours that cattle spend most of their time with; ruminating, resting and grazing. According to the Swedish animal welfare legislation, animals must be kept and cared for in a good environment. The legislation requires cattle to go on pasture, except calves and bulls. The Federation of Swedish Farmers (LRF) has decided to lobby for a change in the grazing legislation. LRF argues that the legislation prevents dairy farmers from developing and being financially competitive internationally. The purpose of this study was to examine consumers' attitudes to an abolished grazing requirement, explain the benefits and disadvantages with pasture for dairy cows and investigate what possible consequences an abolished grazing requirement may mean. To gather information a literature review and a survey study was carried out.